An Innovative and Comprehensive Approach to Nursing Workforce Sustainability in Nova Scotia - Gail Tomblin Murphy, Tara Sampalli, Caroline Chamberland Rowe, Janet Rigby, Cindy MacQuarrie, Adrian MacKenzie and Nancy MacConnell-Maxner (Nursing Leadership, 2022)
The COVID-19 pandemic has revealed long-standing deficiencies with existing nurse recruitment and retention approaches, resulting in critical shortages of nursing capacity that are set to worsen without appropriate action. Decades of evidence and experience suggest that a multi-pronged approach that fosters an enabling and supportive work environment for nurses across all stages of their working lifespan will be required to build a more sustainable nursing workforce. This paper demonstrates Nova Scotia's innovation in creating a comprehensive, evidence-informed approach to nursing workforce planning and management, including key strategic areas of action related to (1) facilitating entry into the workforce, (2) investing in the active workforce and (3) enhancing support for and managing attrition of the workforce. This paper also offers nursing leaders a series of reflections on current learnings in the implementation of this innovative and person-centred approach to nursing workforce sustainability. Recognizing the pressing need for action, Nova Scotia Health and provincial leaders have and are implementing strategic innovations to enhance the nursing workforce. These include: (1) investment in organizational capacity for evidence-based innovation, (2) development of collaborative relationships between both internal stakeholders and community partners and (3) creation of mechanisms for meaningful engagement and co-design of locally relevant innovative solutions.
Keywords: nursing workforce, innovation, sustainability, retention, recruitment